Problematika Pembelajaran Calistung Pada Anak Usia Dini - Aji Jaya Hidayat, Dyah (JOURNAL FASCHO : JURNAL PENELITIAN DAN PENDIDIKAN ANAK USIA DINI, 2023)
Learning calistung for early childhood has always raised pros and cons, especially when it is associated with the Elementary School (SD) curriculum that often changes. On the one hand, there is an assumption that early childhood is a golden age to develop all aspects of child development in a balanced way, so that calistung learning which is synonymous with cognitive aspects will hinder the development of other aspects. Meanwhile, on the other hand, the current tough first-grade curriculum indirectly requires children to master calistung before entering elementary school. This paper discusses the phenomenon of calistung learning in early childhood and things that need to be prepared in accompanying young children in learning calistung. The aim is to describe the problems surrounding calistung in early childhood and their solutions. Qualitative research methods with literature studies are used to reveal this phenomenon. The results of this discussion are that calistung may be taught to early childhood by taking into account the supporting conditions including learning methods, learning readiness and stages of calistung according to child development